Global Risks and Conflicts: The Social, Environmental, and Political Consequences. (September 2019) - Suša, Oleg
Socio-political conflicts relating to survival on this planet have become pressing over the last few decades. Global risks and conflicts are developing within the context of global capitalism with an evident conjunction of environmentally and socially destructive changes. The aim for a critical theory of globalization is to develop further analysis of this conjunction by studying social and ecological crises. Today we see a conflict between environmental justice and risk distribution related to the problems of growing social inequality and poverty. Global capitalism is characterized by an evident conjunction between destructive environmental changes, and social, economic and political (governance) crises. The complex of global transformations brings ever greater interdependence between economic, political, technological, social and environmental processes. Many negative consequences become increasingly unsustainable and less manageable.